Estimating Liver Perfusion From Free–Breathing Continuously Acquired Dynamic Gadolinium-Ethoxybenzyl-Diethylenetriamine Pentaacetic Acid–Enhanced Acquisition With Compressed Sensing Reconstruction. Issue 2 (February 2015) - Chandarana, Hersh; Block, Tobias Kai; Ream, Justin; Mikheev, Artem; Sigal, Samuel H.; Otazo, Ricardo; Rusinek, Henry
Abstract : Objective: The purpose of this study was to estimate perfusion metrics in healthy and cirrhotic liver with pharmacokinetic modeling of high–temporal resolution reconstruction of continuously acquired free-breathing gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid–enhanced acquisition in patients undergoing clinically indicated liver magnetic resonance imaging. Subjects and Methods: In this Health Insurance Portability and Accountability Act–compliant prospective study, 9 cirrhotic and 10 noncirrhotic patients underwent clinical magnetic resonance imaging, which included continuously acquired radial stack-of-stars 3-dimensional gradient recalled echo sequence with golden-angle ordering scheme in free breathing during contrast injection. A total of 1904 radial spokes were acquired continuously in 318 to 340 seconds. High–temporal resolution data sets were formed by grouping 13 spokes per frame for temporal resolution of 2.2 to 2.4 seconds, which were reconstructed using the golden-angle radial sparse parallel technique that combines compressed sensing and parallel imaging. High–temporal resolution reconstructions were evaluated by a board-certified radiologist to generate gadolinium concentration-time curves in the aorta (arterial input function), portal vein (venous input function), and liver, which were fitted to dual-input dual-compartment model to estimate liver perfusion metrics that were compared between cirrhotic and noncirrhotic livers. Results: The cirrhotic livers had significantly lower total plasma flow (70.1 ± 10.1 versus 103.1 ± 24.3 mL/min per 100 mL; P < 0.05), lower portal venous flow (33.4 ± 17.7 versus 89.9 ± 20.8 mL/min per 100 mL; P < 0.05), and higher arterial perfusion fraction (52.0% ± 23.4% versus 12.4% ± 7.1%; P < 0.05). The mean transit time was higher in the cirrhotic livers (24.4 ± 4.7 versus 15.7 ± 3.4 seconds; P < 0.05), and the hepatocellular uptake rate was lower (3.03 ± 2.1 versus 6.53 ± 2.4 100/min; P < 0.05). Conclusions: Liver perfusion metrics can be estimated from free-breathing dynamic acquisition performed for every clinical examination without additional contrast injection or time. This is a novel paradigm for dynamic liver imaging.